The disintegration of patriarchal system expressed by the bourgeois novel's crisis - Attie, Juliana Pimenta [UNESP] (My University, 2012)
The Modern Era is marked by a great revolution in the economic, political and social structure, mainly on account of the sprouting of bourgeoisie, which brings the Bourgeois Novel as a new way to express their feelings and conflicts. In this article, one of the bourgeois characteristics, the patriarchal system, will be discussed. However, the focus will be on its dissolution, which is one evidence of the bourgeois novel's crisis. The word 'crisis' can also be understood as transformation. Thus, in order to illustrate this literary revolution undertaken by women, this article analyses To The Lighthouse, by Virginia Woolf. In this novel, it seems that nothing important happens. However the Stream of Consciousness narrative, with the predominance of Indirect Interior Monologue, psychological time and intertextualities, allows for meaning construal grounded in the dichotomy life/dead. The disintegration of the patriarchal structure is seen from the perspective of power relation between the head of the family and his wife. In addition, a reflection on the role of the woman as an artist is carried out.
Keywords: Feminine writing; Literature about women; Virginia Woolf